PUBLIC PERSPECTIVE ON JUSTICE IN THE PROCESS OF DETAINING SUSPECTS BY INVESTIGATORS - Parlindungan Satria; Robert Pangihutan Radjagoekgoek (Problematika Hukum, 2020)
Humans as legal subjects have rights and obligations in the eyes of the law, having consequences in every action taken by them. The law of criminal procedure (KUHAP) in Indonesia is contained in Law No.8 of 1981, KUHAP, in Article 1 Number 21 where detention is process in the criminal justice system which aims to prevent the perpetrator of a criminal offense from escaping from the place where the perpetrator committed the criminal offense. The research analyses the application of process detention of person who has been named as suspect by investigators does not meet justice from community point of view, because the legal certainty of detention is not equally applied to the community. The case of alleged molestation committed by suspect DC in Bandung and the case of alleged premeditated murder by suspect PC. The suspects have fulfilled all the elements of detention in KUHAP, but the investigators still did not make legal efforts to detain them. The method used is a qualitative approach. Based on the results of the research, the existing detention rules in KUHAP have not evenly provided justice for the community and legal certainty, because the existing legal rules are still multi-interpretation in their application.Keywords: Detention,Investigator, Justice